2016
DOI: 10.1093/nar/gkw1181
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the human KEOPS complex identifies C14ORF142 as a core subunit homologous to yeast Gon7

Abstract: The KEOPS/EKC complex is a tRNA modification complex involved in the biosynthesis of N6-threonylcarbamoyladenosine (t6A), a universally conserved tRNA modification found on ANN-codon recognizing tRNAs. In archaea and eukaryotes, KEOPS is composed of OSGEP/Kae1, PRPK/Bud32, TPRKB/Cgi121 and LAGE3/Pcc1. In fungi, KEOPS contains an additional subunit, Gon7, whose orthologs outside of fungi, if existent, remain unidentified. In addition to displaying defective t6A biosynthesis, Saccharomyces cerevisiae strains har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 45 publications
6
81
0
1
Order By: Relevance
“…This distant sequence similarity strongly supported the observed conditionally dependent protein-protein interactions and suggested that C14ORF142 was indeed likely to substitute for Gon7 within the human complex. Recently, C14ORF142 has been identified as the likely Gon7 ortholog by co-purification with known EKC/KEOPS members [62]. Additionally, the EKC/KEOPS complex was reconstituted in vitro and GST-C14ORF142 was shown to bind directly to the OSGEP-LAGE3 sub-complex validating our prediction.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This distant sequence similarity strongly supported the observed conditionally dependent protein-protein interactions and suggested that C14ORF142 was indeed likely to substitute for Gon7 within the human complex. Recently, C14ORF142 has been identified as the likely Gon7 ortholog by co-purification with known EKC/KEOPS members [62]. Additionally, the EKC/KEOPS complex was reconstituted in vitro and GST-C14ORF142 was shown to bind directly to the OSGEP-LAGE3 sub-complex validating our prediction.…”
Section: Resultssupporting
confidence: 81%
“…The N 6 -threonylcarbamoyladenosine (t 6 A) modification is required for normal cell growth and accurate protein translation in bacteria, archaea, and eukaryotes. While the bacterial and lower eukaryotic components of the EKC/KEOPS complex are known, some of the human subunits are substantially diverged and have only recently been discovered [61, 62]. …”
Section: Resultsmentioning
confidence: 99%
“…4G). As an example, the conserved KEOPS complex that mediates an essential tRNA modification reaction (Wan et al 2016) contained a core catalytic subunit (Kae1) that was essential in all lines, a tightly linked core subunit (TP53RK) essential in nine lines, and three auxiliary subunits essential in four (LAGE3), one (C14ORF142) and zero (TPRKB) lines (Fig. 4H).…”
Section: Essentiality In Human Protein Complexesmentioning
confidence: 99%
“…The core Kae1-TP53RK subcomplex is flanked by the other subunits such that essentiality parallels structural centrality. The evolutionary plasticity of subunit essentiality is illustrated by the observation that Kae1 alone is sufficient for function in the mitochondrion, that three KEOPS subunits are essential in bacteria, and all five KEOPS subunits are essential in yeast (Wan et al 2016).…”
Section: Essentiality In Human Protein Complexesmentioning
confidence: 99%
“…In the first strategy insect cells are infected with multiple types of baculoviruses, each of which carries one or two gene expression cassettes (GECs). This strategy, which involves molecular cloning, is relatively simple and has been successfully applied by many research groups using the pFastBac series vectors (Birnbaum et al, 2014;Chung et al, 2006;Hu et al, 2003;Kee et al, 2010;Wan et al, 2017;Yoo et al, 2009). However, when multiple types of baculoviruses are used, the total number of infectious viruses added to the expression culture should be comparable to the upper limited number of the single baculovirus infection.…”
Section: Introductionmentioning
confidence: 99%